1991
DOI: 10.1007/bf02387744
|View full text |Cite
|
Sign up to set email alerts
|

Fibre orientation and mechanical behaviour in reinforced thermoplastic injection mouldings

Abstract: Process variables, fibre orientation distribution and mechanical properties were inter-related for injection-moulded short-glass fibre-reinforced polypropylene and polyamide and long-glass fibre-reinforced polyamide. The properties of the reinforced grades were also contrasted with those of the base polymer. A rectangular mould with triple pin-edge gates on the same side to facilitate a single melt flow-front or double flow-front advancing adjacently, was employed. Mouldings were evaluated for fibre orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(45 citation statements)
references
References 15 publications
0
45
0
Order By: Relevance
“…In the very centre of the melt the rate of shear is low and the transverse fibre alignment present at the gate is retained. These general features are apparent in studies of fibre orientation distribution found in the (1,3,6,17,23) literature. Figure 7 shows the values of < cos 2 (φ) > obtained from a series of micrographs taken across the thickness of injection moulded tensile bars containing 30% w/w glass fibres.…”
Section: Fibre Orientationmentioning
confidence: 75%
See 1 more Smart Citation
“…In the very centre of the melt the rate of shear is low and the transverse fibre alignment present at the gate is retained. These general features are apparent in studies of fibre orientation distribution found in the (1,3,6,17,23) literature. Figure 7 shows the values of < cos 2 (φ) > obtained from a series of micrographs taken across the thickness of injection moulded tensile bars containing 30% w/w glass fibres.…”
Section: Fibre Orientationmentioning
confidence: 75%
“…The properties of thermoplastic composites result from a combination of the fibre and matrix properties and the ability to transfer stresses across the fibre-matrix interface. Variables such as the fibre content, aspect ratio, strength, orientation and the interfacial strength are of prime importance to the final balance of properties exhibited by injection moulded thermoplastic composites (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Fibre strength may be reduced significantly after fibre formation by damage caused during both the fibre and composite production processes (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…(18) is claimed to be valid for (0.42 < © o < 0.54) using the molding conditions given in the experimental section. Since it is reported at higher injection speeds, melt and molding temperatures polymer composites exhibit a thicker core with a more square flow front, 21) this analysis was beyond the scope of this study since it would require specimen fabrication at many molding conditions.…”
Section: Fiber Orientation Parameter © O Effectsmentioning
confidence: 99%
“…9) In short and long glass fiber polyamide injection-molded rectangular cuboid-shaped plaques, Akay and Barkley correlated longitudinal and transverse fiber flow orientations with tensile and dynamic mechanical and fracture properties. 10) Taking cross sections parallel to the flow line at various depths, they found a 3-layer [skin-core-skin] flow pattern appearing to transition into 5-layers with depth. Core thickness also increased with injection speed, melt and mold temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Core thickness also increased with injection speed, melt and mold temperatures. 10) A typical model used for injection molding simulation is by Hele-Shaw 12) that gives simplified equations for nonisothermal, non-Newtonian, inelastic flows in a thin cavity. Normally the following assumptions are proposed by HeleShaw prior to mathematical modeling: 1) cavity thickness is much less than width; 2) incompressible polymer melt behaves as viscous with no elastics where viscosity is sheardominated; 3) viscous force is much higher than inertia or gravitational forces; 4) in thickness direction, velocity and pressure gradient are zero; 5) no fountain flow exits at flow front; 6) velocity is zero at mold walls; and 7) heat transfer between mold and paste is dominated by conduction then heat transfers into the core by convection.…”
Section: Introductionmentioning
confidence: 99%